The Pre-Eruption State of T Crb as Observed with Alma in 2024 - El Mellah, I (EDP Sciences, 2025)
Context. T CrB is a nearby symbiotic binary and a recurrent nova with a period of around 80 years. The next eruption is expected to take place in 2025 or 2026. As part of a global multi-wavelength campaign on the event, we have obtained time on the Atacama Large mm/sub-mm Array to observe the object between 42 GHz and 407 GHz. Aims. In this first paper on our results, we present our pre-eruption observations made in ALMA frequency Bands 1, 3, 4, 6, 7, and 8 in August to November 2024 and constrain the properties of the environment into which the imminent next nova will erupt. Methods. We calibrated and imaged our ALMA data following the standard ALMA procedures, searched for line emission, and constructed a spectrum from the points for orbital phase 0.43 (August 2024) from 44 GHz to 350 GHz. We compared this with the spectra we measured in the VLA data obtained by Linford et al. in 2016-2017 over the upper half of their frequency range (13.5 GHz to 35 GHz). We created aggregate bandwidth images from all our 2024 data and, for maximum angular resolution, from the band 7 and 8 data, from which we computed an upper limit on the brightness temperature in an annulus with radius 0.8 arcsec – 1.6 arcsec. Results. In the second half of 2024, after the end of its latest high state, the quiescent T CrB was a faint millimeter source with a spectral energy distribution well described by a power law with index α = 0.56 ± 0.11 and a flux density of ca. 0.1 mJy at 44 GHz and 0.4 mJy at 400 GHz. There is no significant line emission. This is in agreement with expectations for free-free emission from the partially ionized wind of the red giant donor star and, in extrapolation to 35 GHz, a factor of 5 fainter than the emission observed in 2016-2017 during the latest high state. Comparing the spectra from that high state between 13.5 GHz and 35 GHz with our spectrum from 2024, our spectrum is softer. The spectral index is on average lower by 0.34 ± 0.11. Our per-band and aggregate bandwidth images of T CrB show an unresolved point source with no evidence of extended structure. Conclusions. A simple model of a free-free emitting, fully ionized stellar wind seems to describe well the 2016-2017 high state of T CrB but not our 2024 ALMA measurements, with their low flux and high turnover frequency suggesting that in 2024 the wind was far from fully ionized. © The Authors 2025.